Nicsp 17 propiedad, planta y equipo y la aplicación presupuestaria del gasto en el Gobierno Autónomo Descentralizado municipal de Machala. - Jaramillo Jaramillo, Andrea Elizabeth (My University, 2021)
The International Public Sector Accounting Standards were issued internationally by the International Public Sector Accounting Standards Council, which were adopted by Ecuador in January 2020, with the purpose of harmonizing the accounting processes of the entities, being important to recognize that the regulations are constantly updated in order to present timely and truthful information on economic activities, therefore, the general objective is to identify the accounting record of the economic fact regarding the acquisition of a vehicle for the transfer of public works personnel in productive activities, through the application of current legal regulations, for the preparation of economic and financial information of non-financial public sector entities. The methodology used was the deductive method, with a qualitative approach, being an investigation with an explanatory design, which allowed the development of the cited case, the bibliographic modality was used as a research technique to search for information. It is concluded that, in the integrated general journal, a type of financial movement was applied, recording in the first accounting entry the commitment and the accrual principle established in NICPS 17 Property, Plant and Equipment and Government Regulations.
Las Normas Internacionales de Contabilidad del sector público se emitieron a nivel internacional por el Consejo de Normas Internacionales de Contabilidad del Sector Público, las misma que fueron adoptadas por Ecuador en el mes de enero del 2020, con el propósito de armonizar los procesos contables de las entidades, siendo importante reconocer que las normativas están en constante actualización con la finalidad de presentar información oportuna y veraz de las actividades económicas, por lo tanto, el objetivo general es identificar el registro contable del hecho económico respecto a la adquisición de un vehículo para el traslado del personal de obras públicas en actividades productivas, mediante la aplicación de las normativas legales vigentes, para elaboración de información económica y financiera de las entidades del sector público no financiero. La metodología que se empleó fue el método deductivo, con enfoque cualitativo, siendo una investigación con diseño explicativo, lo que permitió el desarrollo del caso citado, se utilizó la modalidad bibliográfica como técnica de investigación para la búsqueda de información. Se concluye que, en el diario general integrado se aplicó un tipo de movimiento financiero, registrando en el primer asiento contable el compromiso y el principio de devengado establecidos en la NICPS 17 Propiedad, Planta y Equipo y la Normativa Gubernamental.
Keywords: SECTOR PÚBLICO NO FINANCIERO; CONTABILIDAD GUBERNAMENTAL; CONTABILIDAD GUBERNAMENTAL; NICSP 17 PROPIEDAD